Rapid diagnosis of Talaromyces marneffei infection assisted by metagenomic next-generation sequencing in a HIV-negative patient. (2021) - Zhang, Jingjia; Zhang, Dong; Du, Juan; Zhou, Yang; Cai, Yunting; Sun, Ruixue; Zhou, Jiali; Tian, Jingjing; Wu, Honglong; Lu, Minya; Xu, Yingchun; Yang, Qiwen
Highlights: This is the first case report of diagnosing T. marneffei infection in a HIV-negative patient with the assistance of mNGS in North China. The mNGS was used to diagnose T. marneffei infection much faster than traditional fungal culture. This was a non-HIV patient who infected with T. marneffei . Abstract: Talaromyces marneffei (T. marneffei), is an opportunistic pathogenic fungus commonly reported in southeast Asia. T. marneffei infection predominantly occurs in patients with immunodeficiency and can be fatal if diagnosis and treatment were delayed. Conventional diagnosis of T. marneffei infection relies heavily on tissue culture and histologic analysis, which is time consuming and has limited positive rate. Rapid and accurate diagnosis of T. marneffei remains urgent for effective therapy and prevention. This case is the first reported T. marneffei infection in non-HIV patients in north China diagnosed by mNGS. The successful diagnosis of T. marneffei infection assistant by mNGS underlies the potential of this technique in rapid etiological diagnosis.